Unprecedented Coral Mortality on Southwestern Atlantic Coral Reefs Following Major Thermal Stress - Pereira, Pedro H. C.; Lima, Gislaine V.; Pontes, Antônio V. F.; Côrtes, Luis G. F.; Gomes, Erandy; Sampaio, Cláudio L. S.; Pinto, Taciana Kramer; Miranda, Ricardo J.; Cardoso, Andrei Tiego Cunha; Araujo, Julia Caon; Seoane, José Carlos Sícoli (Frontiers in Marine Science, 2022)
Thermal stress is now considered the major recent cause of coral reef degradation; yet few studies have been conducted describing those effects on Southwestern Atlantic (SWA) reefs. SWA represents a coral endemism hotspot with low-functional redundancy and therefore high extinction risk. Recent research has suggested a “thermal refuge” potential for SWA; however, evidence could suggest a different trend. We report herein an unprecedented coral mortality on the largest coastal Brazilian Marine Protected Area (MPA) following the worst thermal stress event since 1985. Degree Heating Week (DHW) values over 4.0 were observed for 107 days, averaging 8.70 for the period, with a maximum of 12.1. Average live coral cover was reduced of 18.1% while average turf algae cover increase of 19.3%. Mortality was higher for three coral species, with a mean mortality of 50.8% per transect for Millepora braziliensis, 32.6% for Mussismilia harttii and 16.6% for Millepora alcicornis. Our unique data for SWA points that population of two Brazilian endemic species (Millepora braziliensis and Mussismilia harttii) are under severe threat by global warming and coral cover has been dramatically reduced. Hence, concepts of a possible “thermal” refugia for SWA must be taken with caution for this coral endemism hotspot.